Doradztwo jako proces wsparcia zarządzania agrobiznesem - Zawisza, Sławomir (Counseling as Process of Interpersonal Influence, 2005)
The article presents the problems of interpersonal influence in the processes of counseling support of agribusiness managers. Problems of relationships between the counsellor and his clients should be considered according to the rules of interpersonal communication process in counseling. The initiator of using social psychology achievements in counseling theory is Stanley R. Strong who was the first to propose and define the notion of credibility (expertness and trustworthiness) as well as interpersonal attractiveness in the counseling process. Effectiveness of the counsellor's work will be connected with his credibility and attractiveness in the eyes of his clients as well as with his abilities to control the cognitive dissonance reduction processes during the change of opinions and attitudes in counseling interaction.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 446-451